2017
DOI: 10.1016/j.jflm.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Endocan concentrations in postmortem serum, vitreous humor and urine in victims of lethal hypothermia

Abstract: Endocan is a soluble molecule secreted from vascular endothelial cells of various organs. Its exact function in humans remains to be elucidated, though it has been postulated that increased tissue expression or serum levels of this molecule may be an indicator of endothelial activation and neovascularization. In the realm of forensic pathology, studies pertaining to endothelial activation following exposure to cold exclusively focused on thrombomodulin, a transmembrane protein specific to endothelial cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Information regarding biochemical markers that have already been studied but have not demonstrated their significance in the exploration of hypothermic deaths include: urinary histamine, urinary serotonin, blood, vitreous and urinary glucose and blood, vitreous and endocan [12,14,61].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Information regarding biochemical markers that have already been studied but have not demonstrated their significance in the exploration of hypothermic deaths include: urinary histamine, urinary serotonin, blood, vitreous and urinary glucose and blood, vitreous and endocan [12,14,61].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Several studies have shown potential metabolite biomarkers of hypothermia fatalities in the vitreous humor without any pathognomonic sign. A decrease of creatinine without significant perturbation of urea has been reported . Increased ketogenesis, related to heat production, was also reported in the vitreous humor in the case of hypothermia fatalities with high levels of hydroxybutyrate, acetone, and isopropyl alcohol .…”
Section: Introductionmentioning
confidence: 99%